A day when (Almost) nothing happened. (March 2022) - Hollnagel, Erik; Laursen, Tom; Sørensen, Rikke
Highlights: Learning is possible even if "nothing" happens. Safety should learn from how solutions are created by experienced operators. Lessons from resilience engineering can be used to identify critical aspects of successful performance. Analyses of safety related events should go beyond finding the causes and also consider operator responses. Abstract: A fundamental safety management assumption is the need to learn from accidents, to identify their causes, and to take steps to prevent their recurrence. Safety by prevention is, however, not the only solution. Since something cannot go well and fail at the same time, another approach is to learn from situations where things go well and where "nothing" seems to happen. In the present case a computer breakdown led to the loss of most of the information in an air traffic control system. The operators managed to compensate for the missing information and keep traffic flowing, although with reduced capacity, while the technical staff managed to restart the system. The same breakdown occurred two more times during the day but in both cases the operators were able to compensate. In the evening the computer system was restored and no further breakdowns happened. The organisation investigated the event but since it focused on the technical issues the lessons learned were in terms of new checklists, improved procedures, and stricter precautions. The paper presents an analysis from a different perspective that looks at what went well. This identifies a number of things that may contribute to make performance in the future even safer.